The Relationship between Knowledge and Attitudes with Menstrual Hygiene Measures - Mupasi, Restu; Saputra, Evan (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
The purpose of this study was to determine the relationship between knowledge and attitudes with menstrual hygiene practices among female students at SMP Negeri 10 Padang in 2016. This study used an analytic research design with a cross-sectional approach with a sample of 98 class VII students who had experienced menstruation. Data were analyzed using the Chi-Square test with p<0.05. The results showed that less than half of the respondents (42.9%) had sufficient knowledge about menstrual hygiene , more than half of the respondents (54.1%) had positive attitudes towards menstrual hygiene and more than half of the respondents (84.7%) ) had menstrual hygiene measures in the sufficient category. There is a significant relationship between knowledge and menstrual hygiene practices (p=0.017) and there is a significant relationship between attitudes and menstrual hygiene practices (p=0.021).